Gender and culture in a threshold public goods game: Japan versus Canada - C. Bram Cadsby; Yasuyo Hamaguchi; Toshiji Kawagoe; Elizabeth Maynes (Osaka University, Institute of Social and Economic Research (ISER), 2001)
We compare male and female behavior in Japan and Canada in the context of a threshold public goods game with both a strong free-riding equilibrium and many socially efficient threshold equilibria. Although higher rewards produce higher contributions, neither culture nor gender has any significant impact on the equilibrium selected, the amount contributed or the provision success rate. Nonetheless, culture and gender do affect behavior. Japanese females coordinate significantly less closely than Canadian females, while Japanese males coordinate significantly less closely than either Canadian males or Canadian females around an equilibrium. Coordination is related both to conforming and less variable behavior.
Keywords: H41; C92; Z10; J16; 330; threshold public goods; gender; culture; free-riding; Öffentliche Güter; Trittbrettfahrerverhalten; Geschlecht; Kultur; Vergleich; Japan; Kanada